Performance of Xpert HPV on Self-collected Vaginal Samples for Cervical Cancer Screening Among Women in South Africa. Issue 1 (January 2021) - Saidu, Rakiya; Kuhn, Louise; Tergas, Ana; Boa, Rosalind; Moodley, Jennifer; Svanholm-Barrie, Cecilia; Persing, David; Campbell, Scott; Tsai, Wei-Yann; Wright, Thomas C.; Denny, Lynette
Abstract : Objectives: Self-sampling may increase access to cervical cancer screening in low-resource settings. Using Xpert HPV, we compared test performance of self- and clinician-collected samples in HIV-positive and HIV-negative women in South Africa. Materials and Methods: Three hundred thirty HIV-positive and 375 HIV-negative women in the screening group and 202 HIV-negative and 200 HIV-positive women in the referral group, aged 30–65 years, participated in the study. All women self-collected a vaginal sample, and then, a cervical sample was collected by a clinician (both tested using Xpert HPV), followed by colposcopic examination and collection of histologic specimens. Results: There was good agreement between self- and clinician-collected samples for detection of any high-risk human papillomavirus (HPV, κ = 0.72 [95% CI = 0.669–0.771]). Prevalence of HPV and sensitivity of the test to detect cervical intraepithelial neoplasia 2+ was similar in self- and clinician-collected samples. Specificity was lower in self-collected than in clinician-collected samples in both HIV-negative (self: 77.5% [95% CI = 72.8–81.8] vs clinician: 86.9% [95% CI = 82.9–90.2]) and HIV-positive (self: 44.0% [95% CI = 38.0–50.1] vs clinician: 59.7% [95% CI = 53.6–65.6]) women. Restricting the definition of screen-positive to 3 of 5 channels on HPV Xpert improved specificity in both HIV-negative (self: 83.2% [95% CI = 78.8–87.0] vs clinician: 89.7% [95% CI = 86.1–92.7]) and HIV-positive (self: 54.2% [95% CI = 48.1–60.2] vs clinician: 67.4% [95% CI = 61.5–72.9]) women. Conclusions: The self-collected sample had good agreement with the clinician-collected sample for the detection of HPV, and restricting the HPV types may improve the specificity in HIV-positive women.